BLENDED LEARNING PERSPECTIVES FOR STUDENTS (UNIVERSITY EXPERIENCE UNDER CONSTRAINTS DUE TO COVID-19 PANDEMIC) - Goncharov, Vitaly; Stepanova, Diana; Kovalev, Dmitriy; Kovaleva, Tatyana; Batyrshina, Alfiya (Revista Inclusiones, 2020)
Today, measures to prevent the spread of the coronavirus COVID-19 have covered all spheres of life in Russian society and directly influenced the system of organizing the educational process, in particular in higher education. During the COVID-19 pandemic, the integration of technological advances and the educational process has been transformed from modern innovation to an urgent requirement of the time and has undergone intensive development. The study provides a theoretical analysis of the concept of blended learning. Based on an expert survey, the most preferred models of blended learning in the context of the COVID-19 pandemic have been identified, their capabilities and features have been considered, and foreign experience in the implementation of blended learning has been analyzed.